Estimating adjustment costs with data on heterogeneous capital goods - Goolsbee, Austan 1969-; Gross, David B. (1997)
This paper estimates the micro-level costs of adjusting capital using detailed data on investment decisions in the US airline industry. The data include the capital stock retirement, market values, operating costs, and utilization rates of 16 different types of capital goods for each airline. This data on heterogeneous capital goods allows us to estimate the desired stock of capital for each type of plane while controlling for unobserved changes in airline profitability. The results show clear evidence of non-convex adjustment costs inaction for capital investment and quadratic adjustment costs conditional on positive or negative investment. The adjustment costs for utilization show similar non-convexities but with smaller adjustment costs. Aggregating to the firm level or using accounting data obscures the non-convexities and biases the estimated adjustment costs upward.
Keywords: Airlines -- Capital investments; Capital investments -- Decision making; Industrial equipment -- Costs